Pengukuran Kualitas Udara Berbasis IoT Menggunakan NODEMCU V3 dan Sensor MQ135 - Hemiltin Adilah; Budi Tjahjono (Ikatan Ahli Informatika Indonesia, 2025)
Air pollution due to factory activities can have negative impacts on the environment and human health, especially from excessive carbon dioxide (CO?) concentrations. This study aims to design and build an Internet of Things (IoT)-based air quality monitoring system using NodeMCU V3 (ESP-12) and MQ-135 sensors to detect CO? concentrations. This system provides real-time air quality monitoring through the Blynk application and is equipped withnotifications and buzzer alarms if the CO? concentration exceeds the threshold of 2,000 ppm. The data obtained helps identify air quality and provide early warnings regarding the dangers of air pollution. The test results show that the system can work effectively in detecting increasing CO? concentrations and providing notifications as needed, so it can be used as a solution to minimize health risks due to air pollution in factory environments.